A Few Useful Things to Know About Machine Learning. - Domingos, Pedro (Communications of the ACM, 2012)
The author discusses machine learning, also known as predictive analytics or data mining, focusing on lessons for computer science researchers and the use of algorithms to perform computational tasks with more efficiency than manual computer programming. The author argues that all machine learning has to do with representation, evaluation, and optimization. Topics include decision trees, probabilistic guarantees, overfitting, and bias and variance in generalization error. Bayesian model averaging (BMA), scalability, and Boolean domains are mentioned.